HR ANALYSIS TO IMPROVE EMPLOYEE PERFORMANCE USING SWOT AND QUANTITATIVE STRATEGY PLAINING MATRIX (QSPM) METHOD (CASE STUDY OF PT BUMIDA MEDAN) - Afrilinda Lubis, Yeni; Harmain, Hendra; Naser Daulay, Aqwa (JURNAL EKBIS, 2024)
The purpose of this study is to clarify what problems are causing the decline in employee productivity and what can be done to improve employee productivity, as well as to clarify problems related to improving employee productivity and QSPM analysis of improvement strategies. Employee productivity of PT Bumida Medan. PT Bumida Medan is an insurance company that offers various types of insurance products. After observation and discussion with the management of PT Bumida Medan, it was found that among the various problems faced by the staff were many staff who were not disciplined regarding permission to participate. Many employees came late to the office to ask for permission. In addition, the insurance sales plan was not achieved. The insurance sales target also slumped due to higher costs and lower employee productivity. Based on these problems, it can be concluded that the main problem faced by PT Bumida Medan is low employee productivity. To overcome all these problems, the company needs to improve or increase the productivity of its employees. Therefore, this study uses the SWOT approach to determine strategies to improve employee productivity at PT Bumida Medan and among the many alternative strategies to improve employee productivity, the author uses the QSPM technique to evaluate the optimal strategy to be chosen. The results of this study are based on the results of the IFE matrix, indicating that the evaluation of optimal strategies must go through the WT strategy, namely a lack of career ladder, clarifying ranks, manual work methods, maintaining marketing graphics. In addition, the WT strategy in square V explains that companies can use market penetration strategies, as well as HR and product development through clear career ladder training, job promotions, work methods according to needs, modern marketing penetration to increase product sales. The suggestions in this study are expected that PT Bumida Medan can develop a performance improvement plan in order to perform better.